PENDEKATAN BERORIENTASI OBJEK UNTUK PEMODELAN RESPONS SUATU HAMPARAN WIALAYAH PERKOTAAN TERHADAP HUJAN - Pah, Jusuf J. S.; Freitas, Lucelina F. De A.; Hunggurami, Elia (Jurnal Teknik Sipil, 2014)
This work prepared a framework for an object-oriented urban terrain hydrological response model, and was meant to work in conjunction with the preparatory module for urban terrain data capturing, prepared in previous work. This framework engages five classes of object namely terrain cell, clock, precipitation, neighbor identifier and terrain platform. Based on the framework, an object-oriented prototypical model was constructed in MS-Excel environment to demonstrate the workability of the framework. Applying the model on an exemplar case shows that the module mimics well the hydrological response of the terrain and ca accurately replicate the surface run-off response of the terrain. The degree of accuracy was shown to be 95,15% just for a 9 cells modeling. Engaging terrain cells in greater number can yield more accurate results.